2019
DOI: 10.1016/j.neuropsychologia.2019.04.018
|View full text |Cite
|
Sign up to set email alerts
|

Is excessive visual crowding causally linked to developmental dyslexia?

Abstract: For about 10% of children reading acquisition is extremely difficult because they are affected by a heritable neurobiological disorder called developmental dyslexia (DD), mainly associated to an auditory-phonological disorder. Visual crowding is a universal phenomenon that impairs the recognition of stimuli in clutter, such as a letter in a word or a word in a text. Several studies have shown an excessive crowding in individuals with DD, but the causal link between excessive crowding and DD is not yet clearly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
60
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(68 citation statements)
references
References 85 publications
(132 reference statements)
4
60
0
4
Order By: Relevance
“…The individual difference approach of our study expands previous findings, which suggested a dyslexia specific advantage of wider letter spacing (Zorzi et al, 2012;Bellocchi et al, 2019;Bertoni et al, 2019), to readers in a proficiency range that is generally considered normal (152-347 words per minute for standard letter spacing; see Brysbaert, 2019). Future studies should look at a broader range of reading proficiencies to specify under which conditions and for which readers the reduction of single word processing times (in terms of fixation durations) creates benefits that outweigh the disadvantages caused by increased numbers of fixations and reduced skipping.…”
Section: Practical Implications Of Letter Spacing Manipulationssupporting
confidence: 86%
See 1 more Smart Citation
“…The individual difference approach of our study expands previous findings, which suggested a dyslexia specific advantage of wider letter spacing (Zorzi et al, 2012;Bellocchi et al, 2019;Bertoni et al, 2019), to readers in a proficiency range that is generally considered normal (152-347 words per minute for standard letter spacing; see Brysbaert, 2019). Future studies should look at a broader range of reading proficiencies to specify under which conditions and for which readers the reduction of single word processing times (in terms of fixation durations) creates benefits that outweigh the disadvantages caused by increased numbers of fixations and reduced skipping.…”
Section: Practical Implications Of Letter Spacing Manipulationssupporting
confidence: 86%
“…Recent reports that increased spacing between letters improved reading accuracy and oral reading speed of readers with dyslexia instantly, that is, without training (Perea et al, 2012;Zorzi et al, 2012; see also Spinelli et al, 2002), attracted a lot of attention. Several authors interpreted this spacing effect as reflecting an unusual sensitivity of dyslexic readers to crowding (Zorzi et al, 2012;Bellocchi et al, 2019;Bertoni et al, 2019), a phenomenon describing visual discrimination difficulties caused by closely spaced contours (Levi, 2008). Importantly, Zorzi et al (2012) claimed that this increased vulnerability to crowding is specific to dyslexia, since wider letter spacing did not produce significant improvements in a non-impaired control group.…”
Section: Introductionmentioning
confidence: 99%
“…El primer atributo de la infodiversidad está relacionado con una ca racterística fundamental de ésta: la diferencia. La variedad como atri buto de la infodiversidad parte del principio de que la información nue va es producto de información precedente, ya sea registrada en algún soporte o en nuestro cerebro por medio de los sentidos, y esta infor mación que se registra presenta a su vez diferencias de contenido y es tilo, formato, procedencia, lenguaje y soporte, puede ser información de carácter académico o popular, información demandada por el gran público o por el especializado, 36 en suma, todas aquellas diferencias que caracterizan a la información y sus flujos.…”
Section: Variedadunclassified
“…35 Véanse atributos fundamentados en Harrison y Klein, 2007: 11991229. 36 Morales, 2008: 87. 37 El término "meme", en Internet, se refiere a una unidad de información -idea, concepto, situación, expresión o creencia-, manifestado en cualquier tipo de medio y que se replica por medio de Internet -chat, foro, red social, email, entre otros-en forma de imagen, vídeo o frase.…”
Section: Acceso a La Informaciónunclassified
“…De julio a diciembre de 2017 se pre sentaron las estadísticas de estas solicitudes donde se observa que el país que lideró fue EUA con 9 320; en la región de América Latina y el Caribe destacan cuatro países -los cuales se encuentran entre los primeros 20 respecto a la cantidad de solicitudes-: Brasil (1 339), Ar gentina (489), México (239) y Chile (205). 36 El anonimato en Internet puede presentar distintos niveles depen diendo de las características técnicas, de la legislación y de la capa cidad del usuario. Se habla de un anonimato seguro cuando hay pro tección técnica y legal adecuadas.…”
Section: Anonimatounclassified